The Legacy of Vilnius University Professor Audronė Glosienė (1958–2009) as a Book Scholar - Aušra Navickienė; Fausta Kepalienė (Knygotyra)
The article scrutinizes the extensive body of work authored by the late Vilnius University professor, Audronė Glosienė (1958‒2009). The analysis employs a quantitative approach within the broader spectrum of the researcher’s publications. It encompasses a thematic and typological examination while revisiting the circumstances surrounding their inception. To conduct this study, the authors utilize specialized bibliographic tools tailored for this research. These tools adhere to a chronological framework, systematically cataloging the scholar’s diverse publications on book-related themes, including dissertations and students’ theses under her supervision. Additionally, the research incorporates Glosienė’s posthumously compiled document collections, housed in the Manuscripts Department of the Vilnius University Library. Other sources include informative and bibliographic publications chronicling the history of communication and information science over the past three decades, along with insights from colleagues’ memoirs. The findings of this research shed light on the position of Glosienė’s contributions to book studies within the context of Lithuanian academia. They underscore her impact on shaping the next generation of book scholars and graduates across various study programs within the Faculty of Communication at Vilnius University. Furthermore, the study highlights her role in molding the identity of communication and information sciences as an interdisciplinary field that unites various scientific disciplines in Lithuania.